The International Snowboard/Freestyle Ski/ Freeski Competition Rules (ICR) Book VI Joint regulations for Snowboard/Freestyle Ski/ Freeski (FIS, 2020)
BOOK VI JOINT REGULATIONS FOR SNOWBOARD / FREESTYLE SKI / FREESKI SNOWBOARD SLALOM / GIANT SLALOM SNOWBOARD PARALLEL EVENTS SNOWBOARD CROSS SNOWBOARD HALFPIPE SNOWBOARD BIG AIR SNOWBOARD SLOPESTYLE AERIALS MOGULS DUAL MOGULS SKI CROSS FREESKI HALFPIPE FREESKI BIG AIR FREESKI SLOPESTYLE APPROVED BY THE FIS COUNCIL ONLINE MEETING - OCTOBER 2020